2008
DOI: 10.1097/mlg.0b013e31817dfd02
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Pharyngeal Swallowing Function Using High‐Resolution Manometry

Abstract: Aim:This study aimed to demonstrate the feasibility of a novel high-resolution manometry (HRM) system, and to establish normal values of swallowing pressures along the velopharynx and upper esophagus. Methods:Thirty three asymptomatic adult Japanese controls were studied. A solid-state HRM assembly with 36 circumferential sensors spaced 1 cm apart was positioned to record pressures during swallowing from the velopharynx to the upper esophagus. The maximum values of the swallowing (dry and 5 ml of water) pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
1
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(128 citation statements)
references
References 13 publications
4
115
1
8
Order By: Relevance
“…First, researchers have reported that average resting UES pressure was 50-70 mmHg. 12,16,25 Median resting UES pressure in our study was also very similar to that value; 78.8 mmHg (range, 68.8-102.3). Second, if the reference value is set too low, it would be very difficult to distinguish muscular contraction by UES and upper esophageal sphincter.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…First, researchers have reported that average resting UES pressure was 50-70 mmHg. 12,16,25 Median resting UES pressure in our study was also very similar to that value; 78.8 mmHg (range, 68.8-102.3). Second, if the reference value is set too low, it would be very difficult to distinguish muscular contraction by UES and upper esophageal sphincter.…”
Section: Discussionsupporting
confidence: 64%
“…Until recently, researchers have investigated pharyngeal contractility by estimating the peak pharyngeal pressure at 2 anatomical locations; upper and lower pharynx, or velo, meso-, or hypopharynx. 5,12,23 However, peak pharyngeal pressure only shows the highest pressure for a short time and it is difficult to say that it represents the contractility of the whole pharynx. CI was recently developed as a way of quantifying the overall vigor of contraction, and it is known to be sensitive in delineating abnormalities involving sustained or hypertensive esophageal contractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, pressure measurement equipment must have a very short response time [8]. Hence, the pathophysiology of formation of ZD is not clear.…”
Section: Aetiologymentioning
confidence: 99%
“…Although several studies have demonstrated that HRM is useful in identifying the motor behavior of the different elements involved in the pharyngo-esophageal phase of swallowing (97) and the prospect of automatically analyzing this area seems ever closer (98), the current situation shows that:…”
Section: Current Situationmentioning
confidence: 99%